Erythromycin and spiramycin resistance mutations of yeast mitochondria: nature of the rib2 locus in the large ribosomal RNA gene. - Sor, F (1984)
Two linked genetic loci, rib 2 and rib 3, of yeast mitochondrial genome are the sites of mutations that confer resistance to erythromycin and/or spiramycin. We have examined two mutations at the rib 2 locus. Mutation ER354 was found at the nucleotide position 3993 of the large ribosomal RNA gene; it corresponded to a C to G transversion leading to a double resistance to erythromycin and spiramycin. Mutation SR551 was found also at the same position, but the C was replaced by a T, conferring resistance to spiramycin only. Rib 2 and rib 3 are 836 base pairs apart on the gene sequence, but are very close to each other in the secondary structure of ribosomal RNA.